Influence de la densité d'élevage sur la croissance et la qualité de l'huître creuse Crassostrea gigas dans l'étang de Thau - Alunno Bruscia, Marianne; Vercelli, Catherine; Chabirand, Jean-michel; Oheix, Jocelyne; Buestel, Dominique (2001)
We grew Pacific oysters (Crassostrea gigas) in a French Mediterranean coastal breeding area, the Thau lagoon, to examine the influence of stocking density on their growth and quality (i.e. condition index and biochemical composition). Oysters were reared on ropes suspended on a culture table for 15 months between March 1999 to June 2000 at 8 different densities involving two cross factors: the number of ropes per square (NR, i.e. 30, 50,65 and 100 ropes) and the number of oysters per rope (NO, i.e. 78 and 120 oysters). Environmental variables (temperature, salinity, dissolved O2) and trophic conditions (chlorophyll a, suspended particulate matter) were estimated fortnightly to characterise conditions prevailing inside as well as around the experimental table. Growth in total wet mass, shell mass, and wet and dry flesh mass was negatively affected by the number of ropes per square (NR), but not by NO. Condition index (Walne & Mann's index, AFNOR) were also influenced by the stocking density, i.e. the number of ropes per square (NR). Oysters exhibited a lower condition index at high (65 and 100 ropes per square) than at low NR (30 and 50). But, the growth in oyster shell lenght and their biochemical composition (carbohydrate, lipid and protein contents) did not change among the density treatments. Water temperature, salinity, dissolved O2 were found to be homogeneous around the experimental table. The available food for oysters, however, varied significantly around the experimental table which may account for the increasing growth gradient observed between the NW and the SE position on the table. We provide evidence for small-scale patterns of density-dependent growth and quality of C. gigas in Thau. But further predictions of density effects at the basin-scale are still needed. A population dynamics model for the bivalves cultivated in Thau is presently tested and will be useful to assess density effects at the scale of the whole basin culture. Our results, however, suggest that shellfish producers who are ...